The contemporary issues related to conventional treatment of acne and the way forward - Abubakar, Aisha Baffa; Abduljalal, Abdulaziz Sani (Public Health Risk Assesment Journal, 2024)
ABSTRACT Background: People perceive acne as a minority disorder (not a major health concern), but it has a significant impact and burden on the victims. Although conventional drugs are available for its treatment, which are applied directly to the affected skin, such as azelaic acid, benzoyl peroxide, and salicylic acid etc. or  formulationAcne vulgaris is a common skin condition that can have a significant impact on individuals, yet conventional treatments often come with various contemporary issues. This paper discusses the contemporary issues related to the conventional treatment of acne and explores a way forward. Acne vulgaris is a chronic inflammatory disorder of the pilosebaceous unit, with a high prevalence globally and in Nigeria. Although conventional drugs are available for treatment, there are several contemporary issues related to their usage that need to be addressed. Method: Relevant literature, including stakeholder reports and studies conducted globally and locally, were searched and reviewed to identify the contemporary issues related to conventional acne treatment. The key contemporary issues identified include economic, environmental, emotional, social, and spiritual concerns. Findings: The economic burden of costly conventional medications makes them inaccessible for many. Environmental issues arise from the use of potentially harmful chemicals that can pollute water sources and contribute to climate change. Acne can also lead to emotional distress, social stigma, and spiritual conflicts, especially due to the side effects of conventional treatments. Given the limitations of conventional treatments, the article recommends the use of scientifically-proven herbal remedies as a promising alternative strategy. Herbs such as tea tree oil, green tea, chasteberry, black seed, and spikeweed have demonstrated antibacterial, anti-inflammatory, and anti-androgenic properties that can effectively manage acne without the adverse effects of conventional drugs. Conclusion: The use of evidence-based herbal medicines offers a way forward in the treatment of acne, addressing the contemporary issues associated with conventional approaches. Further clinical research and regulatory approval are necessary to integrate these herbal remedies into conventional acne management and ensure their widespread and safe use. Novelty/Originality of this article: This study proposes an integrated acne treatment framework that combines conventional therapies with evidence-based herbal medicine. This approach addresses contemporary issues in acne treatment by considering economic, environmental, and socio-cultural aspects.